A Review of the Research Progress of Orthodontic Archwire Bending Robot for Fixed Appliances - Han Liu; Jingang Jiang; Jingchao Wang; Shan Zhou; Yongde Zhang; Sinan Liu (IEEE Access)
This paper proposes a comprehensive review of orthodontic archwire bending robots for fixed appliances, focusing on their key technologies. Orthodontic archwire bending robots can significantly reduce the workload of orthodontists and enhance the efficiency of orthodontic treatment with compared with the orthodontist’s manual bending of orthodontic archwires. Due to the high degree of customization required for orthodontic archwires and the challenge of springback during bending, research on robotic archwire bending has concentrated on developing advanced robotic systems, optimizing archwire bending plans, and implementing springback compensation methods. This paper comprehensively reviews the advancements in design and control of orthodontic archwire bending robots for fixed appliances. It delves into orthodontic archwire bending planning and springback compensation methods, providing a categorized introduction and detailed summaries. Finally, it evaluates and discusses the challenges and future directions of orthodontic archwire bending robots and their core technologies.